Apologies and Compliment Responses: A Case of Pre-service EFL Teachers - Burcu Turhan (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Apology may be defined as “a compensatory action for an offense committed by the speaker which has affected the hearer” (Marquez-Reiter, 2000, p. 44), and a compliment is another speech act